Screening and mapping of pigments in paintings using scanning electrochemical microscopy (SECM)1. Issue 4 (21st February 2015) - Doménech-Carbó, Antonio; Doménech-Carbó, María Teresa; Silva, Miguel; Valle-Algarra, Francisco Manuel; Gimeno-Adelantado, José Vicente; Bosch-Reig, Francisco; Mateo-Castro, Rufino
<x xml:space="preserve">Abstract</x> The use of the scanning electrochemical microscopy (SECM) technique for identifying and mapping of both organic and inorganic pigments in sub-microsamples from pictorial specimens is described.